MOTIVASI WISATAWAN BERKUNJUNG PADA EVENT WISATA CIAN CUI DI SELATPANJANG KABUPATEN KEPULAUAN MERANTI PROVINSI RIAU - Sattaria Amalina Ulfa; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Tourist motivation is very important, where tourist motivation is an encouragement in a tourist to travel to meet their needs, both biologically and psychologically. This study aims to find out about the Motivation of Tourists at the Cian Cui Tourism Event in Selatpanjang to find out the motivations of tourists visiting the Cian Cui Event in Selatpanjang Meranti Islands Riau Province, to find out the constraints of cian cui event organizers, this research uses descriptive quantitative methods, to describe the problem in tourist visits the sample used was 100 respondents, data collection techniques in this study used observation, interviews, questionnaires and documentation. The results of the study show that Tourist Motivation towards the Cian Cui Event in range score 2598 - 3398                                                             Keywords: Tourist Motivation, Event Cian Cui